PROFILE OF STUDENT PEDAGOGICAL CONTENT ABILITIES INTEGRATED FIELD INTRODUCTION PRACTICE STUDY PROGRAM OF PHYSICS EDUCATION - Muslimin Muslimin (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2020)
This research aims to describe the profile of pedagogical knowledge (PK) capabilities, content knowledge (CK), and pedagogical content knowledge (PCK) of physics students who are conducting integrated field recognition practices (PPLT). This research is qualitative descriptive research, where all data are collected based on facts obtained in the field, so descriptive data were obtained from respondents who were selected. The research subjects involved 6 physics education students who conducted PPLT at school as respondents. The selected category is based on a cumulative achievement index. The selected respondents were 2 high ability students, 2 medium students, and 2 low ability students. Data obtained through pedagogical knowledge observation sheets, content knowledge tests, and pedagogical content knowledge observation questionnaires. The data was taken from PPLT student learning compilation in schools. Based on the results of research on the ability of PK, CK, and PCK PPLT physics education students obtained, that students who have high PK and CK abilities have high PCK abilities, while students who have PK abilities and low CK abilities also have high PCK abilities.